Laparoscopic lavage in a purulent peritonitis model: impact on inflammatory proteins - Erik Sinclair; Maria K. Magnusson; Eva Angenete; Mattias Prytz; Viktor Tasselius; Lena Öhman; Eva Haglind (European Journal of Medical Research)
Abstract Background Laparoscopic lavage is an effective, safe, and feasible treatment in patients with perforated diverticulitis with purulent peritonitis. Laparoscopic lavage was introduced without any detailed knowledge regarding the mechanisms of action. The aim of this study was to validate the reproducibility of an animal model of purulent peritonitis and to study the effect of laparoscopic lavage on inflammatory proteins in this model. Methods Forty rats, divided into eight groups (n = 5) were operated. Six groups underwent cecal ligation and puncture (CLP) causing peritonitis and two groups underwent sham surgery. Three CLP and one sham group received laparoscopic lavage, while the remaining groups acted as time-matched controls. Samples of abdominal fluid and blood were collected after 1, 2 or 3 h and analyzed regarding 92 inflammatory proteins using Olink Target 96 Mouse exploratory panel. Results Animals with peritonitis had higher levels of inflammatory proteins such as CCL3, IL17A and IL6 in abdominal fluid and serum compared to sham. The groups treated with laparoscopic lavage had lower levels of inflammatory proteins in both abdominal fluid and serum compared with untreated peritonitis groups, results were most distinct sampled after one hour. Conclusion Our animal model is reproducible, and mimics perforated diverticulitis with purulent peritonitis with increased levels of inflammatory proteins in abdominal fluid and serum. The levels of several inflammatory proteins were lower following laparoscopic lavage treatment perhaps indicating the physiological effect of laparoscopic lavage. This model can be used to further explore the mechanisms involved in peritonitis and laparoscopic lavage treatment.